Golgi anti-apoptotic proteins redundantly counteract cell death by inhibiting production of reactive oxygen species under endoplasmic reticulum stress. (16th January 2022) - Tang, Xiao-Han; Li, Xin; Zhou, Yan; He, Yu-Ting; Wang, Zhi-Ying; Yang, Xue; Wang, Wei; Guo, Kun; Zhang, Wei; Sun, Yue; Li, Hong-Qing; Li, Xiao-Fang
Abstract : Arabidopsis GAAP1-GAAP4 play redundant positive roles against cell death by regulating glutathione content to inhibit ROS accumulation, and maintaining the unfolded protein response during endoplasmic reticulum stress. Abstract: Maintaining proteostasis in the endoplasmic reticulum (ER) is critical for cell viability and plant survival under adverse conditions. The unfolded protein response (UPR) pathways interact with reactive oxygen species (ROS) to precisely trigger adaptive outputs or cell death under ER stress with varying degrees. However, little information is known about the relationship between UPR signalling and ROS regulation. Here, Arabidopsis GOLGI ANTI-APOPTOTIC PROTEIN1 (GAAP1)-GAAP4 were found to play redundant positive roles under ER stress. Genetic analysis showed that GAAP4 played a role in INOSITOL-REQUIRING ENZYME (IRE1)-dependent and -independent pathways. In addition, GAAPs played negative roles to activate the adaptive UPR under conditions of stress. Quantitative biochemical analysis showed that mutations in GAAP genes decreased the oxidised glutathione content and altered the pattern of ROS and glutathione in early ER stress. When plants were challenged with unmitigated ER stress, mutations in GAAP advanced ROS accumulation, which was associated with a decline in adaptive UPR. These data indicated that GAAPs resist cell death by regulating glutathione content to inhibit ROS accumulation and maintain UPR during ER stress. They provide a basis for further analysis of the regulation of cell fate decision under ER stress.